Business model options for passenger urban air mobility - Straubinger, Anna (CEAS Aeronaut J, 2021)
While technological progress towards passenger urban air mobility (UAM) receives high attention, relevant business models for the deployment of these increasingly sophisticated passenger-carrying air vehicles for urban applications get less attention. However, especially in early market stages with high risks of investment and in respect to an often envisioned implementation of transport services in the proximity of urban settlements, it is important that the technology adds value to society. In this paper relevant perspectives to comprehend the current UAM business environment are presented. Possible operator models and customer segments are compiled and matched in three concrete business model approaches for passenger UAM. Scrutinising UAM Airport Shuttle Services shows that even concepts with sufficient demand might still not be adequate for a valid business case due to incomplete and a so far insufficient critical analysis of the overall operational environment. Second, a so far often unconsidered business model for a Company Shuttle Service is introduced, addressing the problem of scaling up UAM services with a dynamically expandable Business-to-Business (B2B) concept. Third, UAM will be discussed as part of public transport, introducing a business model that is inclusive and in strong line with public demands. Finally, these rather different implementation concepts unlock the space for an open-minded discussion on business models in the field of passenger UAM in general.